Minimally invasive resection is associated with decreased occurrence of early delayed gastric conduit emptying after Ivor-Lewis esophagectomy - Rompen, Ingmar F.; Yilmazcelik, Batuhan; Crnovrsanin, Nerma; Schiefer, Sabine; Jorek, Nicolas; Kantowski, Marcus; Saeedi, Mohammed al; Michalski, Christoph; Peters, Leila; Schmidt, Thomas; Müller, Beat P.; Nienhüser, Henrik (Diseases of the esophagus, 2025)
Early delayed gastric conduit emptying (DGCE) is a frequent complication after Ivor-Lewis esophagectomy (ILE). Despite its relevance, few studies are published using the international consensus criteria. Therefore, we aimed to assess predictors and clinical consequences of DGCE in patients after ILE. This analysis represents a retrospective, single-center cohort study of patients who underwent ILE (2016-2021). DGCE was assessed by the international consensus criteria. Univariable and a multivariable penalized LASSO logistic regression model was applied to identify predictors of DGCE, whereas postoperative outcomes were assessed by group comparisons. The incidence of early DGCE was 15.6% (46/294 included patients). Of all tested preoperatively known and treatment related factors, only minimally invasive surgery was associated with lower odds for the occurrence of DGCE (OR 0.33, 95%CI:0.12-0.77, P = 0.017) when compared to open surgery. When DGCE occurred, the impact on major postoperative morbidity was limited (DGCE 39.1% vs. non-DGCE 33.1%, P = 0.425), especially there were no differences in starting adjuvant treatment (DGCE 50% vs. non-DGCE 46%; P = 0.615) or overall survival (Log-Rank P = 0.995). The results of this study suggest that the impact of DGCE might have been overestimated in the past. The only factor found to be significantly associated with decreased DGCE was minimally invasive surgery. Therefore, individual patient selection for preventive interventions is difficult and routine preventive interventions only seem justified when they can be performed with low adverse outcomes and at low cost. Higher evidence from randomized controlled trials is needed to assess the optimal strategy to prevent and treat DGCE.
Gesehen am 18.08.2025